HEALTH CARE (University of Calgary Press, 1997)
Developed within the context of the expansion of the Canadian welfare state in the years following the Great Depression, the present organization of Canadian health care delivery is now in serious need of reform. This book documents the causes and effects of changes made in this century to Canada's health care policy. Particular emphasis is placed on the decades following 1940, the years in which Canada moved away from an individualistic entrepreneurial medical care system, first toward a collectivist biomedical model and then to a social model for health care.